Atypical Vascular Involvement in a Case of Behçet's Disease - Alejandro Rodríguez Morata; Ana Hidalgo Conde; Carlos de la Cruz Cosme; Susana Gómez Ramírez; Rafael Gómez Medialdea (Case Reports in Surgery)
Introduction. Behçet's disease (BD) is a form of vasculitis of unknown etiology which is rare in our environment. It is characterized by a variety of clinical manifestations and usually affects young adults. Recurrent oral and genital ulcers are a characteristic and extremely frequent symptom, but mortality is linked with more significant symptoms such as aortic pseudoaneurysm, pulmonary pseudoaneurysm, and cerebral venous thrombosis. Patient and Method. We present a case of a young male with atypical BD and severe polyvascular involvement (previous cerebral venous thrombosis and current peripheral venous thrombosis, acute ischemia, and peripheral arterial pseudoaneurysm) who required urgent surgical intervention due to a symptomatic external iliac pseudoaneurysm. Result. The pseudoaneurysm was successfully treated, we performed an iliofemoral bypass, and we treated it with steroids and immunosuppressive therapy. Conclusions. These rare clinical manifestations highlight the importance of considering BD in young patients, even in usual cases of vascular intervention, whether arterial or venous in nature.